Pentoxifylline Treatment of Very Low Birth Weight Neonates with Nosocomial Sepsis - Hamilçıkan, Şahin; Can, Emrah; Büke, Övgü; Erol, Meltem; Gayret, Özlem Bostan (American Journal of Perinatology, 2017)
Objective The objective of this study was to assess the result of intravenous pentoxifylline as an adjunct to antibiotic therapy on mortality and morbidity in very low birth weight (VLBW) preterm neonates with nosocomial sepsis.Methods For the 18 VLBW preterm neonates, as an adjunct therapy to antibiotics regimens, pentoxifylline (5 mg/kg/h for 6 hours) was administered to premature infants with sepsis on 3 successive days. Clinical and laboratory parameters were recorded before and after treatment.Results Following pentoxifylline therapy, the immature-to-total neutrophil ratio and C-reactive protein (CRP) levels were significantly decreased, while the blood pH and base excess were significantly increased (p < 0.05). The axillary temperature, noninvasive blood pressure, hemoglobin, leukocyte, and thrombocyte values did not significantly differ after treatment (p > 0.05). Coagulase-negative staphylococci (CoNS) (32%), Streptococcus hominis (7.3%), Pseudomonas aeruginosa (5.3%), and Candida parapsilosis (3.1%) were identified in the blood cultures. There were no short-term morbidities (intraventricular hemorrhages, necrotizing enterocolitis, periventricular leukomalacia, and patent ductus arteriosus), no adverse effects, and no mortalities during or after the pentoxifylline therapy in the preterm neonate participants.Conclusion The CRP levels and heart rate both decreased, while the pH and base excess parameters of the blood gas analysis changed positively after pentoxifylline treatment in VLBW preterm neonates with nosocomial sepsis.
Keywords: pentoxifylline; nosocomial infection; neonatal intensive care units; very low birth weight infant